Implementation Of Fun Learning Through Mind Mapping Method In History Of Physics Course In Physics Education Department, Universitas Negeri Gorontalo - Payu, Citron S. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study is aimed to identify the difference between the implementation of conventional method and mind mapping method towards students’ learning outcomes in the History of Physics Development course. The sample in this experimental study was selected using a simple random sampling method. Moreover, a test of students’ learning outcomes was employed as the research instruments. The data were analyzed by applying validity, normality, homogeneity, and hypothesis tests. The results show that 8 question items were stated as valid, while the normality test (with chi-square) generated X2count at 7.3582 for the experiment class and X2count = 7.4959 for the control class (X2table = 11.1). The numbers indicate that both of the classes were normally distributed and the data were homogenous, as the X2counts = 0.2302 ≤ X2table = 11.1. Further, the hypothesis t-test generated that tcount = 79.9237 > ttable = 1.6752; the numbers indicate a significant difference between the learning outcomes in experiment and control class. All in all, this study concludes that the mind mapping method yields higher performance than the conventional method; in other words, there is a significant difference between the experimental class and the control class.